2021
DOI: 10.3390/ijerph18179330
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide, Oxidative Stress and Streptococcus mutans and Lactobacillus Bacterial Loads in Saliva during the Different Stages of Pregnancy: A Longitudinal Study

Abstract: Hormonal changes associated with pregnancy promote oral bacterial growth, which may affect salivary nitric oxide (NO) levels, oxidative stress (OS), and antioxidant capacity (AC). We hypothesized that caries-related bacterial load, NO level, and OS in the saliva change with advancing gestation. The aim of this study was to investigate longitudinal changes in salivary NO, OS, and AC during pregnancy and correlate them with Streptococcus mutans (SM) and Lactobacillus (LB) colonization at different stages of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As elucidated by [ 45 ], the observed elevation in salivary estrogen levels during the second and third trimesters theoretically suggests a potential impact on the expression profiles of specific microbial and protein markers. In line with this, nitric oxide increased with advancing gestation, but the oxidative stress and the antioxidant capacity did not change significantly during pregnancy [ 46 ]. Some of the antimicrobial peptides displayed dynamic fluctuations, while others maintain a consistent pattern throughout the course of pregnancy and postpartum assessments [ 47 ].…”
Section: Discussionmentioning
confidence: 79%
“…As elucidated by [ 45 ], the observed elevation in salivary estrogen levels during the second and third trimesters theoretically suggests a potential impact on the expression profiles of specific microbial and protein markers. In line with this, nitric oxide increased with advancing gestation, but the oxidative stress and the antioxidant capacity did not change significantly during pregnancy [ 46 ]. Some of the antimicrobial peptides displayed dynamic fluctuations, while others maintain a consistent pattern throughout the course of pregnancy and postpartum assessments [ 47 ].…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, Streptococcus mutants was also found in pregnant women who had never used orthodontic appliances. The changes in these bacteria [ 29 ] are related to increased levels of oxidative stress such as malondialdehyde (MDA) [ 28 ], and cause a decrease in the salivary acidity and calcium content [ 30 ]. Due to this condition, the risk of dental caries and gingival disease increases.…”
Section: Discussionmentioning
confidence: 99%